An analytical study of the solidification in a semi-infinite porous medium - Rai K.N.; Rai S. (My University, 2025)
A solidification process taking place in a solid, porous half-space is defined. A boundary fixing technique has been developed to solve this free boundary problem. Exact solutions for the frozen-moisture concentration, the temperature and moisture distributions as well as the location of the moving solidfication front are obtained. The whole analysis is presented in a dimensionless form and the results, thus obtained, are shown graphically. The characteristic of the solidification process is that there exists a discontinuity of the moisture concentration across the moving solidification front, and that the frozen-moisture concentration is always higher than the liquid-vapor concentration. © 1992.